Reconstructing a B-Cell Clonal Lineage. II. Mutation, Selection, and Affinity Maturation - Kepler, Thomas B.; Munshaw, Supriya; Wiehe, Kevin; Zhang, Ruijun; Yu, Jae-Sung; Woods, Christopher W.; Denny, Thomas N.; Tomaras, Georgia D.; Alam, S. Munir; Moody, M. Anthony; Kelsoe, Garnett; Liao, Hua-Xin; et al. (Frontiers in Immunology, 2014)
Affinity maturation of the antibody response is a fundamental process in adaptive immunity during which B cells activated by infection or vaccination undergo rapid proliferation accompanied by the acquisition of point mutations in their rearranged immunoglobulin (Ig) genes and selection for increased affinity for the eliciting antigen. The rate of somatic hypermutation at any position within an Ig gene is known to depend strongly on the local base sequence, and Ig genes have region-specific codon biases that influence the local mutation rate within the gene resulting in increased differential mutability in the regions that encode the antigen-binding domains. We have isolated a set of clonally related natural immunoglobulin heavy chain-light chain pairs from an experimentally infected influenza patient, inferred the unmutated ancestral rearrangements and the maturation intermediates, and synthesized all of the antibodies using recombinant methods. The lineage exhibits a remarkably uniform rate of improvement of the effective affinity to influenza hemagglutinin (HA) over evolutionary time, increasing 1000-fold overall from the unmutated ancestor to the best of the observed antibodies. Furthermore, analysis of selection reveals that selection and mutation bias were concordant even at the level of maturation to a single antigen. Substantial improvement in affinity to HA occurred along mutationally-preferred paths in sequence space and was thus strongly facilitated by the underlying local codon biases.